Predictors of Children’s Literacy: A Meta-Analysis Study Alphabet of Knowledge - Martha Christianti; Tri Hartiti Retnowati; Sri Wening (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2023)
Alphabetic skills were one of the early literacy skills.  Several studies on alphabetic skills have been conducted in Indonesia. Meta-analysis was used to describe the children's alphabet skills aged 3 to 6 years as an aggregate. The maximum likelihood estimation method and random effect design were performed to aggregate children's alphabetic skills that can be generalized in Indonesia. The articles were obtained from research published between 2014 and 2021. Those were accessed and collected through a collection of bachelor's thesis on Google Scholar and university digital libraries. The meta-analysis was carried out with JASP. The results showed that the ability to recognize letters among children aged 3 to 6 years in Indonesia was 50.16 (scale 0-100). Despite the fact that mastering letters has an impact on children’s growth in early literacy, the study’s findings show that youngsters in Indonesia still have a low level of letter recognition. These results encourage to improve the quality of kindergartens literacy instruction in Indonesia